Flow Towards A Stagnation Region Of A Curved Surface In A Hybrid Nanofluid With Buoyancy Effects - Ishak, Anuar; Waini, Iskandar; Pop, Ioan (MDPI AG, 2021)
This paper examines the impact of hybrid nanoparticles on the stagnation point flow towards a curved surface. Silica (SiO2) and alumina (Al2O3) nanoparticles are added into water to form SiO2 Al2O3/water hybrid nanofluid. Both buoyancy-opposing and -assisting flows are considered. The governing partial differential equations are reduced to a set of ordinary differential equations, before being coded in MATLAB software to obtain the numerical solutions. Findings show that the solutions are not unique, where two solutions are obtained, for both buoyancy-assisting and -opposing flow cases. The local Nusselt number increases in the presence of the hybrid nanoparticles. The temporal stability analysis shows that only one of the solutions is stable over time